Er islamismen populistisk, eller er populismen i Mellemøsten blevet islamistisk? - Simonson, Jørgen Bæk (Politik, 2017)
The article discusses and compares different types of populism that have characterized certain political developments in the Middle East since the beginning of the 20th Century. It is concluded that non-militant Islamism has played a crucial part in this development and secured widespread public support. This has been the case in Iran where the circle around Khomeini specifically articulated the struggle against the Shah in relation to Shiitic Islamism.